ETV6‐LPXN fusion transcript generated by t(11;12)(q12.1;p13) in a patient with relapsing acute myeloid leukemia with NUP98‐HOXA9. Issue 3 (6th November 2015) - Abe, Akihiro; Yamamoto, Yukiya; Iba, Sachiko; Kanie, Tadaharu; Okamoto, Akinao; Tokuda, Masutaka; Inaguma, Yoko; Yanada, Masamitsu; Morishima, Satoko; Mizuta, Shuichi; Akatsuka, Yoshiki; Okamoto, Masataka; et al.
Abstract : ETV6, which encodes an ETS family transcription factor, is frequently rearranged in human leukemias. We show here that a patient with acute myeloid leukemia with t(7;11)(p15;p15) gained, at the time of relapse, t(11;12)(q12.1;p13) with a split ETV6 FISH signal. Using 3′‐RACE PCR analysis, we found that ETV6 was fused to LPXN at 11q12.1, which encodes leupaxin. ETV6 ‐ LPXN, an in‐frame fusion between exon 4 of ETV6 and exon 2 of LPXN, did not transform the interleukin‐3‐dependent 32D myeloid cell line to cytokine independence; however, an enhanced proliferative response was observed when these cells were treated with G‐CSF without inhibition of granulocytic differentiation. The 32D and human leukemia cell lines each transduced with ETV6 ‐ LPXN showed enhanced migration towards the chemokine CXCL12. We show here for the first time that LPXN is a fusion partner of ETV6 and present evidence indicating that ETV6‐LPXN plays a crucial role in leukemia progression through enhancing the response to G‐CSF and CXCL12. © 2015 Wiley Periodicals, Inc.